Pengaruh Promosi dan Kemanan Berbelanja Terhadap Minat Beli Konsumen pada Situs Belanja Online Blibli.com di Kota Batam - Widodo, Slamet; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2023)
This study aims to determine the effect of promotion, shopping safety on consumer buying interest on the Blibli.com online site in Batam city. In this study using quantitative descriptive analysis and quantitative multiple regression analysis. The sample data studied totaled 101 samples obtained from data collection using a link questionnaire which was distributed to respondents via social media and directly. The accidental sampling technique is the technique used for sampling in this study where all people who happen to meet researchers can be sampled if they meet the characteristics needed by researchers. The results of this study indicate that the promotion and security variables partially and simultaneously have a significant effect on consumer buying interest.